Pendidikan Anti Korupsi: Studi terhadap Konsep Worldview dan Korupsi - Amrullah, Khasib; Khakim, Usmanul; Haryanto, Haryanto; Listriana, Listriana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
It is undeniable that corruption has become a serious problem for the state of Indonesia. Academic attention to the corruption cannot be underestimated; in which many research reports on corruption are published in scientific journals; which generally look from the perspective of the standing law or religion. Different from these studies, this study will try to examine the concept of corruption from a philosophical point of view through the philosophical theory that has become popular recently i.e worldview theory. Worldview itself is understood as a belief system that guides human life; which can be used as a framework in reading the facts of corruption. This study is expected to be able to provide an explanation of the fundamental structure of the concept of corruption and compile the elements of an Islamic worldview needed in anti-corruption education. This research is library research; data obtained from books, papers and other documentation. The data analysis technique uses the contain analysis method, which is trying to interpret what is written in the text. In addition, comparative analysis will also be used between one text and another. The results of this study are: First, in the Islamic worldview the concept of corruption is closely related to metaphysical concepts such as the concept of God, Sharia (God's rules), sin, the afterlife, reckoning (hisab), retribution; while still affirming concepts in the worldly dimension such as the concept of the state, property, law and justice. Second, these concepts should be included in anti-corruption education.